The Influence of Internalization of Character Education (Religious Values, Teacher's Example, Honesty and Discipline) Against Social Piety - Riyanto, Riyanto; Siregar, Maragustam; Hasyim, A. Dardiri (Universitas Muhammadiyah Ponorogo, 2024)
The research objectives are: 1. To analyze the internalization of religious values, teacher example, student honesty and student discipline in students at SDIT Al Huda, SDMPK and SDIU Al Amanah Kab. Wonogiri. 2. The influence of religious values, teacher example, honesty and discipline on social piety among students at SDIT Al Huda, SDMPK and SDIU Al Amanah Kab. Wonogiri.The research method is mixed method and correlational study, which is to test the hypothesis about the relationship between variables or to state the magnitude of the relationship between the two variables. The population in this study were 234 students of grade VI of SDIT Al Huda, SDMPK and SDIU Al Amanah, Wonogiri Regency. While the sample used was part of the total population of the study. The sampling of the study used a 5% error rate, according to Sugiyono, with a population of 234, the sample to be studied was 140 students. The data collection methods used were observation, questionnaires and interviews. The data analysis technique used was linear regression analysis.Research results: 1) Internalization of Religious Values, Teacher Exemplary, Student Honesty, and Student Discipline in Students at SDIT Al Huda, SDMPK and SDIU Al Amanah Kab. Wonogiri has gone through various adaptations. 2) There is a significant influence of religious values, teacher example, honesty and discipline on social piety among students at SDIT Al Huda, SDMPK and SDIU Al Amanah Kab. Wonogiri, the higher a student's character value, the better their level of social sobriety.